2021
DOI: 10.1016/j.bpj.2021.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Membrane hydrophobicity determines the activation free energy of passive lipid transport

Abstract: The collective behavior of lipids with diverse chemical and physical features determines a membrane's thermodynamic properties. Yet, the influence of lipid physicochemical properties on lipid dynamics, in particular interbilayer transport, remains underexplored. Here, we systematically investigate how the activation free energy of passive lipid transport depends on lipid chemistry and membrane phase. Through all-atom molecular dynamics simulations of 11 chemically distinct glycerophospholipids, we determine ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(56 citation statements)
references
References 92 publications
1
55
0
Order By: Relevance
“…Consistent with this idea, we find that the hydrophobic tails of lipids in close proximity to both the apo and C1P-bound forms of CPTP are oriented more parallel to the membrane surface than expected for a POPC membrane without CPTP bound (Fig 5 Another membrane property that is especially key to lipid transport is the hydrophobicity of a lipid's local membrane environment. We previously demonstrated that the activation free energy for passive lipid transport correlates with the average number of hydrophobic contacts a lipid makes with surrounding membrane lipids, ⟨n CC ⟩ mem [26]. As ⟨n CC ⟩ mem decreases, the rate of passive lipid desorption from a membrane increases [26].…”
Section: Cptp Alters the Membrane's Physical Properties To Facilitate...mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this idea, we find that the hydrophobic tails of lipids in close proximity to both the apo and C1P-bound forms of CPTP are oriented more parallel to the membrane surface than expected for a POPC membrane without CPTP bound (Fig 5 Another membrane property that is especially key to lipid transport is the hydrophobicity of a lipid's local membrane environment. We previously demonstrated that the activation free energy for passive lipid transport correlates with the average number of hydrophobic contacts a lipid makes with surrounding membrane lipids, ⟨n CC ⟩ mem [26]. As ⟨n CC ⟩ mem decreases, the rate of passive lipid desorption from a membrane increases [26].…”
Section: Cptp Alters the Membrane's Physical Properties To Facilitate...mentioning
confidence: 99%
“…An additional puzzle is how CPTP overcomes the significant free energy barrier for lipid desorption from a membrane, which limits passive lipid transport rates [21][22][23][24][25]. We recently demonstrated that the activation free energy barrier for passive lipid desorption reflects the thermodynamic cost of breaking hydrophobic lipid-membrane contacts [25], and that it can be lowered by decreasing the hydrophobicity of the transferring lipid's local membrane environment [26]. Thus, we hypothesize that CPTP rapidly extracts C1P from a membrane by disrupting C1P-membrane hydrophobic contacts, thereby lowering the free energy barrier for lipid desorption and catalyzing C1P transport.…”
Section: Introductionmentioning
confidence: 99%
“…across the plasma membrane with moderate metabolic energy and fast migration speed. [30][31][32][33] Notably, the merits of high-efficiency ion transport and structural stability are the desired characteristics for AZIB cathode materials.…”
Section: Introductionmentioning
confidence: 99%
“…In lipid exchange mediated by “basket”-shaped LTPs that shuttle lipids back and forth by diffusion or tethered diffusion, the rate-limiting step for the transfer of a lipid from one membrane to another is the extraction or desorption from the membrane itself rather than the LTP-assisted transport ( Dittman and Menon, 2017 ; Wong et al, 2017 ). Spontaneous desorption of a lipid into the aqueous phase and henceforth between two membranes is energetically costly (∼10–20 kCal/mol) and extremely slow (several days) ( Rogers et al, 2021 ). Local membrane composition, lipid packing and membrane order also affects the energetics of lipid desorption ( Rogers et al, 2021 ).…”
Section: Vectoring and Energizing Lipid Exchange At Membrane Contact Sites And Within Membranes: “Passive” Versus “Actmentioning
confidence: 99%
“…Spontaneous desorption of a lipid into the aqueous phase and henceforth between two membranes is energetically costly (∼10–20 kCal/mol) and extremely slow (several days) ( Rogers et al, 2021 ). Local membrane composition, lipid packing and membrane order also affects the energetics of lipid desorption ( Rogers et al, 2021 ). LTPs lower the desorption energy barrier as they partition the lipid from a bilayer into a hydrophobic binding pocket instead of bulk aqueous solvent.…”
Section: Vectoring and Energizing Lipid Exchange At Membrane Contact Sites And Within Membranes: “Passive” Versus “Actmentioning
confidence: 99%